2016
DOI: 10.1007/s12602-016-9238-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrogen Peroxide, Lactic Acid, and Surfactants from Vaginal Lactobacilli on the Antibiotic Sensitivity of Opportunistic Bacteria

Abstract: We studied as hydrogen peroxide, lactic acid, or surfactants from clinical isolates of vaginal lactobacilli and cell-free supernatants from probiotic strain LCR35 can influence on the sensitivity of opportunistic bacteria to antibiotics. We found that the most effective in increasing sensitivity to antibiotics were hydrogen peroxide and surfactants or their combination but no lactic acid. In some cases, the effect of the composition of hydrogen peroxide and surfactants was clearly higher than the sum of effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 52 publications
1
8
0
2
Order By: Relevance
“…Kongnum and Hongpattarakere (2012) found that hydrogen peroxide was a major agent contributing to the antibacterial effect of Lactobacillus plantarum MRO3.12. Interestingly, Sgibnev and Kremleva (2017) found that hydrogen peroxide produced by probiotic vaginal lactobacilli were effective in increasing sensitivity to antibiotics, suggesting that hydrogen peroxide producing LAB in combination with antibiotic‐producing species may be more effective for pathogenic growth inhibition. The antimicrobial activity of LAB shrimp probiotic Streptococcus phocae PI80 has been shown to be due to the production of the bacteriocin Phocaecin PI80, which inhibits the growth of a range of Gram‐positive and Gram‐negative bacteria, including Listeria monocytogenes , Vibrio spp., Aeromonas hydrophila and Pseudomonas aeroginosa (Satish Kumar & Arul, 2009).…”
Section: Probiotic Bacteriamentioning
confidence: 99%
“…Kongnum and Hongpattarakere (2012) found that hydrogen peroxide was a major agent contributing to the antibacterial effect of Lactobacillus plantarum MRO3.12. Interestingly, Sgibnev and Kremleva (2017) found that hydrogen peroxide produced by probiotic vaginal lactobacilli were effective in increasing sensitivity to antibiotics, suggesting that hydrogen peroxide producing LAB in combination with antibiotic‐producing species may be more effective for pathogenic growth inhibition. The antimicrobial activity of LAB shrimp probiotic Streptococcus phocae PI80 has been shown to be due to the production of the bacteriocin Phocaecin PI80, which inhibits the growth of a range of Gram‐positive and Gram‐negative bacteria, including Listeria monocytogenes , Vibrio spp., Aeromonas hydrophila and Pseudomonas aeroginosa (Satish Kumar & Arul, 2009).…”
Section: Probiotic Bacteriamentioning
confidence: 99%
“…The literature suggests that the main advantages associated with H 2 O 2 activity are its ability to cross the cell membrane of the pathogen, to damage the membrane, proteins, DNA, and enzymes by the formation of free radicals and the anti-inflammatory stimulus of the vaginal mucosa [ 79 81 ]. Furthermore, the joint action of metabolites, such as H 2 O 2 , organic acids, bacteriocins, and biosurfactants, has already been attributed as a potent antibiotic-assisting tool to contain genital infections and minimize resistance to antibiotics [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been published on antimicrobial activity of lactic acid produced by lactobacilli against pathogen microorganisms (Şanlıbaba and Güçer, 2015;Arqués et al, 2015;Sgibnev and Kremleva, 2016). The antimicrobial activity of organic acids is directly related to the pH reduction and its ability to dissociate.…”
Section: Antimicrobial Activity Of Cfs Smentioning
confidence: 99%
“…The beneficial action of lactobacilli has been widely described in several reports which focus on their viable cells and cell free supernatants (CFS) (Mariam et al, 2014;Lau and Liong, 2014). The CFS is a well-known source of bioactive compounds such as antioxidants, bacteriocins, surfactants, organic acids, H 2 O 2 , CO 2, and low molecular weight peptides (Lau and Liong, 2014;Sgibnev and Kremleva, 2016). Their biosynthesis depends on the factors linked to growth such as pH, temperature, O 2 tension, and culture medium composition (Zalán et al, 2010).…”
Section: Introductionmentioning
confidence: 99%